Effect of menstrual irregularity on academic performance of undergraduate students of Debre Berhan University: A comparative cross sectional study - Enguday Demeke; Abayneh Birlie Zeru; Esubalew Tesfahun; Woineshet Bedru Mohammed (PLoS ONE, 2023)
Background Menstrual period is a critical time in the life of females. For the first few years after menarche, irregular cycle is common due to premature hypothalamic-pituitary ovarian (HPO) axis physiologically. If persistent, it becomes a major problem in student’s life. But few studies conducted on effect of menstrual cycle irregularity on academic performance among university students were descriptive. However assessing the effect of menstrual irregularity on academic performance by using average grade point approach is critically important to magnify its effect. Objective To compare effects of menstrual irregularity on academic performance among undergraduate students of Debre Berhan University, Ethiopia 2020. Methods A comparative cross sectional study was conducted among 404 students in Debre Berhan University, Ethiopia, 2020. A standard tool of menstrual cycle regularity which is prepared by international federation of gynecologist and obstetrics (IFGO) was used to screen students who have menstrual irregularity. Independent sample t- test was done to compare the mean difference of academic performance between the two groups of students. Results The age of study participants ranges between 18 and 26 years with a mean age of 20.69 ± 1.43 years. The mean age at menarche was 14.9 ± 1.67 ranging from 9 to 18 years. Students who had menstrual irregularity had mean average grade point (AGP) of (2.78 ± 0.57) and students who had regular menstruation had mean AGP of (2.97 ± 0.53). Students who had menstrual irregularity had lower mean average grade point by a mean difference of 0.19 (95%CI: 0.09–0.30). Conclusion This study found that students who had menstrual irregularity had significantly lower mean AGP as compared with students who had regular menstruation.